Design and synthesis of selective and potent orally active S1P5 agonists. - Dev, Kumlesh (My University, 2010)
The immunomodulatory drug fingolimod (FTY720, 2-amino-2-[2-(4-octylphenyl)ethyl]propane-1,3-diol), derived from a fungal metabolite (ISP-1, myriocin), is phosphorylated in vivo by sphingosine kinases to produce (R)-FTY720-phosphate(FTY720-P). FTY720-P activates sphingosine-1-phosphate(S1P) receptors S1P1, S1P3, S1P4, and S1P5 at low nanomolar concentrations and is inactive toward the S1P2 receptor. The FTY720-P-mediated activation of the S1P1 receptor on lymphocytes induces receptor internalization, which attenuates T-cell response to S1P gradients, preventing their egress from secondary lymphoid tissues. In addition to playing a role in the immune system, all S1P receptors except S1P4 are also found differentially expressed in the central nervous system and on various tumor cell types. Although the precise regulation of these receptors by locally released S1P remains unclear, S1P receptors are thought to play a role in such events as astrocyte migration, oligodendrocyte differentiation, and cell survival and neurogenesis. To assess the relevance of individualS1P receptor subtypes for the activity of FTY720-P, selective agonists are required. Because S1P5 receptors are expressed on oligodendrocytes, and S1P5 receptors are thought to play a role in oligodendrocyte differentiation and survival, we focused on the development of S1P5 agonists.
PUBLISHED
Keywords: Agonists; FTY720; Myelination; Oligodendrocytes; Receptors; Sphingosine; Neuroscience